The anticancer agent 3-bromopyruvate: a simple but powerful molecule taken from the lab to the bedside - Silva, J. Azevedo (2016)
At the beginning of the twenty-first century, 3-bromopyruvate (3BP), a simple alkylating chemical compound was presented to the scientific community as a potent anticancer agent, able to cause rapid toxicity to cancer cells without bystander effects on normal tissues. The altered metabolism of cancers, an essential hallmark for their progression, also became their Achilles heel by facilitating 3BP's selective entry and specific targeting. Treatment with 3BP has been administered in several cancer type models both in vitro and in vivo, either alone or in combination with other anticancer therapeutic approaches. These studies clearly demonstrate 3BP's broad action against multiple cancer types. Clinical trials using 3BP are needed to further support its anticancer efficacy against multiple cancer types thus making it available to more than 30 million patients living with cancer worldwide. This review discusses current knowledge about 3BP related to cancer and discusses also the possibility of its use in future clinical applications as it relates to safety and treatment issues.